Pengalaman Anak Mantan Pekerja Seks Komersial dalam Mencapai Resiliensi - Yany Ludia Natasian; Wiwin Hendriani (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2021)
There are many immoral behaviors that are in the spotlight in Indonesia and affect the morality of the nation's children. One of them is working as a Commercial Sex Worker. Being the child of a former Commercial Sex Worker is not an easy thing to accept. This study aims to explore and interpret the experiences of children of former commercial sex workers in achieving resilience. This research is a qualitative research with a phenomenological approach. The research design used is interpretative phenomenological analysis. The study was conducted in the city of Surabaya, involving 2 participants who are children of former commercial sex workers. The researcher analyzed the interview transcripts and produced several themes. Through this research, it is known that achieving resilience for children of former commercial sex workers is not easy and there are 2 major factors that affect a person's ability to achieve resilience, namely protective factors and risk factors. This study also found that internal and external motivation is needed to help someone achieve resilience in a certain period of time.